High Quality Maize Centromere 10 Sequence Reveals Evidence of Frequent Recombination Events - Wolfgruber, Thomas K.; Nakashima, Megan M.; Schneider, Kevin L.; Sharma, Anupma; Xie, Zidian; Albert, Patrice S.; Xu, Ronghui; Bilinski, Paul; Dawe, R. Kelly; Ross-Ibarra, Jeffrey; Birchler, James A.; Presting, Gernot G. (Frontiers in Plant Science, 2016)
The ancestral centromeres of maize contain long stretches of the tandemly arranged CentC repeat. The abundance of tandem DNA repeats and centromeric retrotransposons (CR) have presented a significant challenge to completely assembling centromeres using traditional sequencing methods. Here we report a nearly complete assembly of the 1.85 Mb maize centromere 10 from inbred B73 using PacBio technology and BACs from the reference genome project. The error rates estimated from overlapping BAC sequences are 7 x 10-6 and 5 x 10-5 for mismatches and indels, respectively. The number of gaps in the region covered by the reassembly was reduced from 140 in the reference genome to three. Three expressed genes are located between 92 and 477 kb of the inferred ancestral CentC cluster, which lies within the region of highest centromeric repeat density. The improved assembly increased the count of full-length centromeric retrotransposons from 5 to 55 and revealed a 22.7 kb segmental duplication that occurred approximately 121,000 years ago. Our analysis provides evidence of frequent recombination events in the form of partial retrotransposons, deletions within retrotransposons, chimeric retrotransposons, segmental duplications including higher order CentC repeats, a deleted CentC monomer, centromere-proximal inversions, and insertion of mitochondrial sequences. Double-strand DNA break (DSB) repair is the most plausible mechanism for these events and may be the major driver of centromere repeat evolution and diversity. This repair appears to be mediated by microhomology, suggesting that tandem repeats may have evolved to facilitate the repair of frequent DSBs in centromeres.